Comparison of Semen Characteristics of Good and Poor Freezable Jersey Crossbred Bulls - Perumal, P.; Barik, A. K.; Mohanty, D. N.; Das, S.; Mishra, P. C.; Chang, S. (International Journal of Bio-resource and Stress Management, 2016)
A study was conducted to assess the semen quality parameters in good and poor freezable Jersey crossbred bulls. The experimental bulls were 4−6 years of age with good body condition (score 5−6) selected and were maintained under optimum nutrition and managemental practices as per the standard criteria fixed for maintenance of breeding bulls in bull stations. In this study, six bull were selected and were divided into good (n=3) and poor (n=3) freezable bulls based on seminal characters of the post thaw semen. The bulls have been classified into good and poor freezable depending upon the criteria of producing semen with ≥50% (good freezability) and <50% (poor freezability) post-thaw sperm motility. Good freezable semen could withstand satisfactorily the deep freezing temperature while the poor freezable semen could not do so and lost some of their seminal characteristics after thawing. The semen was collected by AV method and a total of 36 ejaculates, 6 ejaculates from each bull were collected for assessment. The following seminal parameters were taken for the experimental study namely volume (ml), mass activity (grade), individual motility (per cent), sperm concentration (X106 ml-1), live sperm (per cent), total sperm abnormality (per cent), loss of acrosomal integrity (per cent) and plasma membrane integrity by hypo-osmotic swelling test (HOST; per cent). The result revealed that there was a highly significant difference (p<0.01) prevailed in sperm concentration while significant difference (p<0.05) was observed in the other seminal parameters between good and poor freezable bull semen.